Text analytics of unstructured textual data: A study on military peacekeeping document using R text mining package - Zainol, Zuraini; Nohuddin, Puteri N.E.; Mohd, Tengku A.T.; Zakaria, Omar (2017)
This paper describes a technique of text analytics on peacekeeping documents to discover significant text patterns exist in the documents. These documents are considered as unstructured textual data.The paper proposes a framework that consists of 3 stages (i) data collection (ii) document preprocessing and (iii) text analytics and visualization.The technique is developed using R text mining package for text analytics experiments.